Teachers’ Attitudes toward Transition Services from School to Work by Students with Mild Intellectual Disabilities - Erum Aslam Khan; Muhammad Javed Aftab (JCTE, 2024)
Transitioning refers to a range of activities that help students transition from high school to post-secondary education, work, and independent life. A student's Individualized Education Plan (IEP) includes a section on transformation planning. The IEP team will work with your kid to determine their talents and interests in order to build this program. The Individuals with Disabilities Education Act is the legislation that governs the program for individuals with disabilities (IDEA). Teachers' opinions of the effects of moving from school to employment This research focused on students with modest intellectual impairments. It is the goal of this study to discover how special education teachers' views on the availability of transitional assistance affect their students' ability to find employment. Data was gathered through the use of a questionnaire in this study. Demographic and inferential data were employed to help shed light on the investigation's central question(s). In order for individuals with minor intellectual impairments who obtain an Individualized School Plan (IEP) to succeed in job or education, the results of data analysis are required. Some believe that job placement is closely related to transition planning. There were two sections in the questionnaire: the first contained preliminary information and the second contained an opinion regarding the impact of transition services and their use. Due to the privilege of covid 19 in southern Punjab, an online survey was done. SPSS version 2020 and statistical tests like t-Test ANOVA and mean were used to analyze data from 101 participants. There is a substantial correlation between instructors' professional qualifications and transition planning, according to the data (90 percent). The study also found that (95 percent) teachers believe that transitional plans need to be improved through the use of feedback. Discussion shows that allowing students to be self-sufficient in school is essential.